Oral Vanoxerine Prevents Reinduction of Atrial Tachyarrhythmias: Preliminary Results - Cakulev, Ivan (2011)
BACKGROUND: Vanoxerine is a promising, new, investigational antiarrhythmic drug. The purpose of this study was to test the hypothesis that oral dosing of vanoxerine would first terminate induced atrial flutter (AFL) and atrial fibrillation (AF), and then prevent their reinduction. METHODS: In five dogs with sterile pericarditis, on the fourth day after creating the pericarditis, we performed electrophysiologic (EP) studies at baseline, measuring atrial excitability, refractoriness (AERP) and conduction time (CT) when pacing from the right atrial appendage, Bachmann’s bundle (BB), and the posteroinferior left atrium at cycle lengths (CLs) of 400, 300 and 200 ms. Then, after induction of AFL or AF, all dogs received hourly oral doses of vanoxerine: 90 mg, followed by 180 mg and 270 mg. Blood was obtained to determine plasma vanoxerine concentrations at baseline, every 30 minutes, when neither AFL nor AF were inducible, and, finally, one hour after the 270 mg dose. Then we repeated the baseline EP studies. RESULTS: Four dogs had inducible, sustained AFL, and one dog only had induced, nonsustained AF. In four AFL episodes, oral vanoxerine terminated the AFL and then rendered it noninducible after an average of 111 minutes (range 75–180 minutes) after the first dose was administered. The mean vanoxerine plasma level at the point of noninducibility was 84 ng/ml, with a narrow range of 76–99 ng/ml. In the dog with induced, nonsustained AF, it was no longer inducible at a drug level of 75 ng/ml. Vanoxerine did not significantly: 1) prolong the AERP except at BB, and then only at the faster pacing CLs; 2) change atrial excitability thresholds; 3) prolong atrial conduction time, the PR interval, the QRS complex or the QT interval. CONCLUSIONS: Orally administered vanoxerine effectively terminated AFL and rendered it noninducible. It also suppressed inducibility of nonsustained AF. These effects occurred at consistent plasma drug levels. Vanoxerine’s insignificant or minimal effects on measured electrophysiologic parameters are consistent with little proarrhythmic risk.